Relationships of thrombosis and fibrinolysis to atherosclerosis. - Hamsten, A; Eriksson, P; Karpe, F; Silveira, A (1994)
The importance of the haemostatic system in predisposing to or precipitating coronary heart disease has gained increasing recognition. Major advances have been made in our understanding of the mechanisms resulting in hypercoagulability and impaired fibrinolytic function. Emphasis is placed on the role of dyslipoproteinaemia and insulin resistance.